Człowiek a współczesna technika - kto kim steruje? = Man and modern technique - who controls who? - Grobelny, Michał; Grobelna, Iwona (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the modern world, we are surrounded by technical solutions, with which we constantly communicate and interact. Devices and systems are supposed to help us in our work, everyday life and entertainment. However, are their roles reduced to mechanized servants? Authors try to show how human relationships with modern technology look like and how they affect the human person. They also try to determine who is controlling whom.
Keywords: człowiek; maszyna; relacje; sterowanie; internet; man; machine; interaction; control